EFFECTIVENESSOF LABOUR ANALGESIA WITH LOW DOSE OF KETAMINE- A COMPARATIVE STUDY (CAHIERS MAGELLANES-NS, 2024)
INTRODUCTION: Labour is always connected with a painful experience even though it’s a natural physiological process. Ketamine originally called as CI 581 was first synthesized by Calvin Stevens in 1962 and was found to provide adequate analgesia even at sub anesthetic dose. The present study was designed to compare the efficacy of low dose ketamine versus placebo in providing adequate analgesia during labour. MATERIAL AND METHODS: This study was a hospital based comparative study which was conducted in the labour room in the Department of Obstetrics and Gynaecology at Aarupadai Veedu medical college and hospital, Puducherry. Totally 60 participants were enrolled in the study,30 in each group the interventional group was administered low dopse of ketamine with loading dose 0.2mg/kg followed by 0.1 mg/kgas maintenance dose as infusion while controlled group was administerd saline infusion. The data was analysed using SPSS software P value less then 0.05 consider as statistically significant.RESULT: In our study the pain relief was excellent in study group. The mean pain score during delivery among patients in ketamine group was comparatively lower when compared to placebo group showing statistical significance with p<0.001 at 1hr,2hr,3hr,4hr and 5hr respectively. The satisfaction score among patients among ketamine and placebo group was found to be significant with p<0.010CONCLUSION: It provides effective analgesia in low dose and does not cause respiratory depression. Intravenous ketamine in low dose appears to be safe alternative to epidural analgesia and had no complications to mother and fetus.